2019
DOI: 10.5435/jaaos-d-17-00447
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling for Geriatric Hip Fracture Patients: Early Surgery and Delirium Have the Largest Influence on Length of Stay

Abstract: Background: Averaging length of stay (LOS) ignores patient complexity and is a poor metric for quality control in geriatric hip fracture programs. We developed a predictive model of LOS that compares patient complexity to the logistical effects of our institution's hip fracture care pathway. Methods:A retrospective analysis was performed on patients enrolled into a hip fracture comanagement pathway at an academic level-one trauma center from 2014-15. Patient complexity was approximated using the Charlson Comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…They stated that the timeliness of surgical intervention in this population causes no effect on overall complications, readmissions, or 30-day mortality, but an admission-to-operation time of >48 hours is associated with costly increases in LOS. Hecht et al 15 developed a predictive model for LOS in geriatric hip fracture patients and found that for each day surgery was delayed, LOS increased by 0.75 days. The totality of the results of from our study and aforementioned studies suggest that hospitals and provider teams continue to investigate possible interventions to mitigate unnecessary delays to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that the timeliness of surgical intervention in this population causes no effect on overall complications, readmissions, or 30-day mortality, but an admission-to-operation time of >48 hours is associated with costly increases in LOS. Hecht et al 15 developed a predictive model for LOS in geriatric hip fracture patients and found that for each day surgery was delayed, LOS increased by 0.75 days. The totality of the results of from our study and aforementioned studies suggest that hospitals and provider teams continue to investigate possible interventions to mitigate unnecessary delays to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined hip fractures admitted to trauma centers or examined national healthcare databases. 9 10 11 12 13 Their findings have been helpful in the evaluation of processes and procedures at larger tertiary care centers and have been informative in establishing clinical operating guidelines, including the use of dedicated orthogeriatric comanagement. 12 , 14 However, these resources are not always readily available at smaller community-based hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in 2019, Hecht, et. al 10 published a report attempting to construct a predictive model for geriatric hip fracture patients. They found that reduced time to surgery and absence of delirium were predictors of shorter LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical factor in reducing morbidity in hip fractures is timely surgery. 34 - 38 To achieve this, the Orthopaedic Trauma Service—comprised of fellowship-trained employed faculty—was invited to participate in the program. As the hospital is also a level I trauma center, this created availability for an all-day trauma room during the week.…”
Section: Methodsmentioning
confidence: 99%